Arbuscular cell invasion coincides with extracellular vesicles and membrane tubules - Roth, Ronelle; Hillmer, Stefan; Schumacher, Karin (Nature plants, 2019)
During establishment of arbuscular mycorrhizal symbioses, fungal hyphae invade root cells producing transient tree-like structures, the arbuscules, where exchange of photosynthates for soil minerals occurs. Arbuscule formation and collapse lead to rapid production and degradation of plant and fungal membranes, their spatiotemporal dynamics directly influencing nutrient exchange. We determined the ultra-structural details of both membrane surfaces and the interstitial apoplastic matrix by transmission electron microscopy tomography during growth and senescence of Rhizophagus irregularis arbuscules in rice. Invasive growth of arbuscular hyphae was associated with abundant fungal membrane tubules (memtubs) and plant peri-arbuscular membrane evaginations. Similarly, the phylogenetically distant arbuscular mycorrhizal fungus, Gigaspora rosea, and the fungal maize pathogen, Ustilago maydis, developed memtubs while invading host cells, revealing structural commonalities independent of the mutualistic or parasitic outcome of the interaction. Additionally, extracellular vesicles formed continuously in the peri-arbuscular interface from arbuscule biogenesis to senescence, suggesting an involvement in inter-organismic signal and nutrient exchange throughout the arbuscule lifespan.
Gesehen am 11.07.2019